A Retrospective Narrative Study of Pre-Service Teachers' Language Barrier Experiences in International Teaching Practicum - Iswatun Chasanah; Sumardi Sumardi (Universitas Hamzanwadi, 2022)
The present retrospective narrative study reported in this article explores the international teaching practicum program has become a new trend in a lot of university-based English as a Foreign Language (EFL) teacher education programs, particularly in Southeast Asian countries. This phenomenon led to the high demand for university-based EFL teacher education programs of having international networking which aims to give more cross-cultural understanding and experience for the pre-service teachers in teaching EFL abroad. This retrospective narrative case study aims to investigate the language socialization experiences and challenges of two Indonesian pre-service EFL teachers during the teaching practicum program in Thailand. The data was collected through participants’ teaching practicum documents and semi-structured interviews. Grounded in a retrospective narrative study and Relational Turning Point Events (RTPEs) theoretical framework, this study is hoped to provide a better understanding of the EFL teaching development, particularly for preparing pre-service teachers for intercultural teaching practicum.